Effects of Lower Temperature on Expression and Biochemical Characteristics of HCV NS3 Antigen Recombinant Protein - Chen-Ji Huang (MDPI AG, 2021)
The nonstructural antigen protein 3 of the hepatitis C virus (HCV NS3), commonly-used for HCV ELISA diagnosis, possesses protease and helicase activities. To prevent auto-degradation, a truncated NS3 protein was designed by removing the protease domain. Firstly, it was overexpressed in E. coli by IPTG induction under two different temperatures (25 and 37 °C), and purified using affinity chromatography to attain homogeneity above 90%. The molecular mass of purified protein was determined to be approx. 55 kDa. While lowering the temperature from 37 to 25 °C, the yield of the soluble fraction of HCV NS3 was increased from 4.15 to 11.1 mgL−1 culture, which also improved the antigenic activity and specificity. The protein stability was investigated after long-term storage (for 6 months at −20 °C) revealed no loss of activity, specificity, or antigenic efficacy. A thermal stability study on both freshly produced and stored HCV NS3 fractions at both temperatures showed that the unfolding curve profile properly obey the three-state unfolding mechanism. In the first transition phase, the midpoints of the thermal denaturation of fresh NS3 produced at 37 °C and 25 °C, and that produced after long-term storage at 37 °C and 25 °C, were 59.7 °C, 59.1 °C, 55.5 °C, and 57.8 °C, respectively. Microplates coated with the fresh NS3 produced at 25 °C or at 37 °C that were used for the HCV ELISA test and the diagnosis outcome were compared with two commercial kits—Abbott HCV EIA 2.0 and Ortho HCV EIA 3.0. Results indicated that the specificity of the HCV NS3 produced fresh at 25 °C was higher than that of the fresh one at 37 °C, hence showing potential for application in HCV ELISA diagnosis.